2013
DOI: 10.3389/fpsyg.2013.00767
|View full text |Cite
|
Sign up to set email alerts
|

Experience and generalization in a connectionist model of Mandarin Chinese relative clause processing

Abstract: Sentences containing relative clauses are well known to be difficult to comprehend, and they have long been an arena in which to investigate the role of working memory in language comprehension. However, recent work has suggested that relative clause processing is better described by ambiguity resolution processes than by limits on extrinsic working memory. We investigated these alternative views with a Simple Recurrent Network (SRN) model of relative clause processing in Mandarin Chinese, which has a unique p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 52 publications
3
36
2
Order By: Relevance
“…An open question for future work has to do with animacy. The animacy configuration used in this study is uncommon because (i) the heads of our object‐extracted RCs are animate, whereas corpus findings show object‐extracted RCs typically have inanimate heads (Hsiao & MacDonald, ; Wu et al., ), and (ii) our passivized subject‐extracted RCs contain an inanimate instrument following BEI, whereas Chinese passive construction typically requires an animate agent. Thus, future work might employ more common animacy configurations to see whether the conclusion still holds.…”
Section: Discussionmentioning
confidence: 90%
“…An open question for future work has to do with animacy. The animacy configuration used in this study is uncommon because (i) the heads of our object‐extracted RCs are animate, whereas corpus findings show object‐extracted RCs typically have inanimate heads (Hsiao & MacDonald, ; Wu et al., ), and (ii) our passivized subject‐extracted RCs contain an inanimate instrument following BEI, whereas Chinese passive construction typically requires an animate agent. Thus, future work might employ more common animacy configurations to see whether the conclusion still holds.…”
Section: Discussionmentioning
confidence: 90%
“…In the materials used in previous experiments, several local ambiguities might have confounded the results (for a discussion of local ambiguities in Chinese RCs also see Lin & Bever, 2006;Lin & Bever, 2011;Qiao, Shen, & Forster, 2012;Vasishth et al, 2013). Indeed, Hsiao and MacDonald (2013) and Hsiao, Li, and MacDonald (2014) have argued that the results of previous studies on Chinese RCs can be largely explained by the local ambiguities in the stimuli. Thus, although the theoretically interesting aspect of Chinese relative clauses lies in the diametrically opposed predictions of the expectation-based account vs the memory-based accounts, it is vital to bring the local ambiguities under experimental control before we can investigate these opposing predictions.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, we expect a significantly shorter processing time for ORC at the second noun, relativizer de, and main clause verb if working memory capacity affects the retrieval of the subject/object in relative clauses (Gibson, 1998;Hsiao & Gibson, 2003). On the other hand, we expect faster processing of SRCs if frequency and experience with relative clauses dominate readers' processing (Hsiao & MacDonald, 2013;Jäger et al, 2015;Lin & Bever, 2006;Vasishth et al, 2013). We will examine these effects at the relativizer de, second noun, and main clause verb regions.…”
Section: Current Studymentioning
confidence: 99%
“…Researchers have found that Chinese SRCs are easier to process and comprehend than ORCs in a series of self-paced reading and eye-tracking experiments (e.g., Jäger, Chen, Li, Lin, & Vasishth, 2015;Lin & Bever, 2006;Vasishth, Chen, Li, & Guo, 2013). They argue that the findings support experience-based or frequentist theories: because SRCs are more frequent than ORCs in Chinese, readers have been exposed to SRCs more and thus process and comprehend Chinese SRCs more quickly and easily (Gennari & MacDonald, 2008;Hsiao & MacDonald, 2013;Levy, 2008).…”
Section: Chinese Relative Clauses Processingmentioning
confidence: 99%
See 1 more Smart Citation